Outcomes focused user involvement in social work education: applying knowledge to practice. Issue 8 (16th November 2016) - Levy, Susan; Aiton, Rowan; Doig, Jade; Dow, John P. L.; Brown, Shireen; Hunter, Liz; McNeil, Ryan
Abstract: This paper discusses an innovative approach connecting service user and carer involvement (SUCI) in social work education to social work practice. The research team, comprised service users, carers, social work students and module leader, worked collaboratively democratising the research process. At the University of Dundee, a core social work module facilitates students to spend 15 h with a service user and/or carer (host) gaining a unique insight into their everyday lives. During this time, hosts and students discuss two policy practice questions, responses to these questions are generating annual qualitative data, with study findings being disseminated at local and national level. The experiential learning students acquire from spending time with their host becomes the site of knowledge creation through involvement that is applied to practice. This paper reports on the narratives emerging from the longitudinal data (2012–2015, n = 90) on the changing landscape of social care in Scotland and the dissemination of project findings. We explore the intersection where the voices of service users and carers, student learning and social work practice coalesce. A model of outcomes focused SUCI is introduced as a template for meaningful, sustainable and outcomes-focused SUCI in social work education.